Vaishnavismo e espiritismo: possíveis equivalências conceituais em uma história conectada - Araújo, Albério Campos de (2016)
This work is a study on the religious traditions, Vaisnavism Gaudhya and Spiritism. We seek a comparative analysis between the terms chosen within the two traditions, which are: God, Soul, reincarnation, suffering and liberation. The general objective is the search for a conceptual approximation between different words and a possible interlocution. According to the bibliographical study developed, it is possible to demonstrate the similarity between concepts and ideas common to both traditions, as well as a panorama about the history of each one. Have been used for the theoretical background the Bhagavad-Gita of A.C Bhaktivendanta Swami and the version of the German Indologist Georg Feuerstein, in confrontation to the Book of Spirits of Allan Kardec. The used method was the analysis of the primary sources cited and the comparison between the terms present in the two strands, resulting in the finding that there are equivalences between the concepts chosen for analysis as well as differences in the field of interpretation.